An Unoperated Crouzon Family Treated with Monobloc Distraction: Challenges and Lessons. Issue 11 (2nd November 2021) - Hart, Justin; Lu, Stephen; Gasteratos, Konstantinos; Chaiyasate, Kongkrit
Abstract : Background: Crouzon syndrome (CS) is a rare form of craniosynostosis characterized by bicoronal craniosynostosis and facial features including severe midface hypoplasia, exophthalmos, and hypertelorism. Most patients are diagnosed and treated in early childhood; however, there are a few reports of Crouzon patients treated as adults with monobloc facial advancement. To our knowledge, this is the first report of a family affected by CS treated sequentially with monobloc facial advancement using combined internal and external distraction osteogenesis (rigid external distraction). Methods: We present a family from Jamaica (mother 47 years old, older daughter 17, and younger daughter 9) who were brought to our craniofacial clinic with stigmata of CS and no previous surgical intervention. Patients had bicoronal craniosynostosis and exorbitism, with varying severity, sequelae, and comorbidities. Here, we delineate our technique of monobloc distraction osteogenesis with advancement osteotomies using dual "push–pull" method, elevation of a split anteriorly based tunneled pericranial flap to seal off nasal cavity, and internal and external distraction. Results: Our patients had favorable outcomes after reconstruction to reduce ocular symptoms and improve midface hypoplasia and aesthetic appearance. No intracranial injury, hardware/soft-tissue infection, hardware failure, or (new) loss of vision were encountered in 10 months follow-up. Conclusions: Dual "push–pull" monobloc distraction is safe and effective for a range of ages in CS; it allows good vector control, accommodates patient compliance, and allows early rigid external distraction device removal with sufficient time for consolidation. This surgery can be performed with highly satisfactory results.